(untitled) (International Journal of Innovative Technologies in Economy, 2025)
The internationalization of small and medium-sized enterprises (SMEs) in Algeria has become increasingly vital for enhancing competitiveness and market diversification. However, these enterprises face significant challenges, including limited resources and inadequate market information, which hinder their export efforts (Ruzzier; Hisrich, 2007). This study addresses the gap in the existing literature by exploring the potential role of artificial intelligence (AI) in assessing the specific needs of Algerian SMEs in their export endeavors. The research objectives include evaluating how AI can assist in identifying these needs and analyzing its impact on enhancing export performance. To achieve these objectives, a mixed-methods approach is employed, combining quantitative surveys with qualitative interviews to gather comprehensive data from SME leaders. The findings reveal that AI tools significantly improve the accuracy of need assessments compared to traditional methods and facilitate better decision-making processes for SMEs. Furthermore, the study highlights key insights into how AI can optimize export strategies, thereby contributing to a deeper understanding of the internationalization challenges faced by Algerian SMEs.In conclusion, this research underscores the importance of integrating AI into the support mechanisms for SMEs, offering practical recommendations for policymakers and business leaders to enhance the internationalization process. The implications of these findings suggest that leveraging AI can lead to more effective strategies for navigating global markets.